A Multicentre, Observational Study of Sodium Picosulfate and Magnesium Citrate as a Precolonoscopy Bowel Preparation - Jonathan Love; Edmond-Jean Bernard; Alan Cockeram; Lawrence Cohen; Martin Fishman; James Gray; David Morgan (Canadian Journal of Gastroenterology)
BACKGROUND: Sodium picosulfate with magnesium citrate (PSMC) has been available as a precolonoscopy bowel preparation in Canada since 2005. A high patient acceptability and preference appears to have contributed to its wide adoption across the country. Despite its frequent use, there are relatively few published studies of this product, especially reports regarding its use in routine clinical practice. Moreover, to date, there have been no Canadian studies of any kind.